Inteligência competitiva e cooperação em arranjos produtivos locais: um estudo no setor moveleiro de Uberlândia - Siqueira, Wender Rodrigues de (2014)
The present circumstances, of intense competition, has compelled companies to seek alternatives to enhance their competitiveness. In this context, the information gains an strategic prominent role within the organizations seeking to provide competitive advantage through competitive intelligence. So, there is a growing need for relevant, accurate, timely and reliable information about the competitive environment. The information, seen as a relation with the social environment, requires the existence of shared codes that are recognized by those involved. Its value within organizations has resulted in the emergence of agglomerations of companies engaged in similar activities. Such change has made that the investigations on Clusters gained prominence in organizations and in academy, raising researches like this one, which seek to understand the synergies generated by interactions between companies within common environments. Taking into consideration the above context, this study presented as its purpose to identify and to analyze the perception of the entrepreneurs of Cluster furniture of Uberlândia City, in relation to the interest and availability in the sharing of strategic information and of intelligence, about the organizational macro and microenvironment. The specific objectives, also presented in the study, consider the following neeeds: to show the perception of importance for the Cluster companies on the components of the organizational macro and microenvironment; to verify the perception of Cluster´s entrepreneurs on the sharing of strategic information, cooperation and competitive intelligence; to point out and to investigate the perception of the Cluster´s entrepreneurs on the hierarchy of the components of the organizational macro and microenvironment in the potentiation of competitiveness of their business; and to identify and to analyze the interrelations among the components of the organizational macro and microenvironment that characterize the entrepreneurs perceptions on the importance of the access to information and, also, in relation to the interest of these in sharing strategic information and intelligence. The study is characterized as a quantitative and qualitative research, and we have adopted, as research strategies, the bibliographic research, the documentary research and the survey. The data sources used are: the bibliography related to the topic on study, the documents related to the creation of the Furniture producing area and the owners of the furniture companies in Uberlândia. As techniques for collecting of applied data, we have: bibliographical survey, documentary research, a questionnaire and interviews. In relation to the techniques of data analysis, we have adopted the literature review, the use of documental analysis, descriptive statistics, statistical inference and analysis factorial. The components of the organizational macro and microenvironment used in this study were based on the division proposed by Moresi (2001a) and adapted for Lopes, De Muÿlder and Judice (2011), which contemplates 14 components: clients; competition at the Cluster level; competition at the level of the organization; suppliers; funding and promotion lines; new entrants; regulatory agencies; substitute products; economic environment; legal environment, environmental legislation; political environment; social, demographic and cultural aspects; environment; and technological trends. Through the factorial analysis, it was verified the extraction of four factors related to the importance of access to information and five factors for the interest of sharing information. In a general way, it can be inferred that there is the interest and the availability of entrepreneurs of the furniture Cluster of Uberlândia in sharing strategic information and of intelligence, on the organizational macro and micro environment. However, currently, the exchange of information is still incipient. This shows the necessity of being created mechanisms that facilitates the interaction between companies.